Comunicação pública, transparência e políticas públicas: avaliação de informações em portais brasileiros de governo - Rothberg, Danilo [UNESP]; Liberato, Fabíola de Paula (My University, 2013)
An expansion of the professional field of Public Relations can be seen nowadays, influenced by factors such as the increasing use of information and communications technologies for the dissemination of information on public management and the potential creation of dialogue between government and citizens. Despite this trend, there is still a need for specific knowledge about normative aspects of public communication generated by governments on the internet and its role in the fulfillment of the right to information. This article offers a contribution to fulfill the gap of guidelines and standards for professional performance. It describes the results of empirical research which identified the potential contribution of government web portals of the main cities of São Paulo, in the southeastern Brazil, to the strengthening of citizenship, considered in its dimension of exercising the right to information about public policies, particularly those which have an impact on education. The depth and breadth of information were investigated according with twelve categories of evaluation: history; diagnoses; goals; goals; resources and current actions; planned resources and actions; efficiency; effectiveness; impact; cost-effectiveness; user satisfaction; and equity. The data found on the analyzed portals correspond to the average of 11% of which was considered, under the theoretical-methodological context of the research, as information necessary to comprise the full characterization of a public policy in relation to the categories of assessment. Opportunities to improve government web portals were detected, for which we suggest communication management strategies.

Verifica-se atualmente a ampliação do campo de atuação dos profissionais de Relações Públicas, influenciada por fatores como o uso crescente das tecnologias de informação e comunicação para a difusão de informações sobre gestão pública e o potencial estabelecimento de diálogo entre o poder público e os cidadãos. A despeito desta tendência, nota-se ainda a necessidade de conhecimento específico sobre aspectos normativos da comunicação pública gerada por governos na internet e seu papel para o atendimento do direito à informação. Este artigo oferece uma contribuição para o atendimento dessa lacuna de orientações e normas de atuação profissional. São descritos os resultados de pesquisa empírica que identificou a potencial contribuição dos portais eletrônicos das principais cidades do Estado de São Paulo, na Região Sudeste do Brasil, à afirmação da cidadania, considerada em sua dimensão de exercício do direito à informação sobre políticas públicas, em particular aquelas de impacto sobre a educação. A profundidade e a abrangência das informações foram pesquisadas em relação a doze categorias de avaliação: antecedentes; diagnósticos; objetivos; metas; recursos e ações atuais; recursos e ações planejadas; eficiência; eficácia; impacto; custo-efetividade; satisfação do usuário; equidade. Os dados encontrados nos portais analisados correspondem à média de 11% do total que, no contexto teórico-metodológico da pesquisa, foi considerado como informação necessária para abranger a totalidade da caracterização de uma política pública, em relação às categorias de avaliação propostas. Oportunidades de aperfeiçoamento dos portais foram detectadas, para as quais sugerimos estratégias de gestão da comunicação.
Public communications, transparency, and public policy: assessing information on Brazilian government web portals
Keywords: Public communication; Government web portals; Right to information; Public relations; Citizenship; Comunicação pública; Governo eletrônico; Direito à informação; Relações públicas; Cidadania